3D printed biocompatible polylactide-hydroxyapatite based material for bone implants; Materials and Manufacturing Processes; Vol. 33, iss. 16 - Petrovskaya T. S. Tatyana Semyonovna; Toropkov N. E. Nikita Evgenievich; Mironov E. Evgeny; Azarmi F. Fardad (2018, 2018)
Title screen